2005
DOI: 10.2166/wst.2005.0139
|View full text |Cite
|
Sign up to set email alerts
|

Development of a distributed hydrological model based on urban databanks – production processes of URBS

Abstract: The objective of this study is to present a distributed hydrological model especially dedicated to urban catchments, and able to represent hydrological processes usually neglected in urban modelling, such as evapotranspiration, infiltration in roads, or direct infiltration of soil water in sewers. This model, called URBS (as Urban Runoff Branching System) is distributed considering the spatial variability of land use which is well known thanks to urban databanks managed by GIS. The production function is detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…These methods will often overestimate runoff and underestimate the recharge to groundwater (Ragab et al 2003) and do not reflect the complex pattern of urban water balance in the long term. (Rodriguez et al 2005), for example, have shown that there is a considerable variation in the runoff coefficient with different rainfall conditions while (Davies & Hollis 1981) showed that when the water balance is considered over a long period, evaporation, infiltration and depression storage may be more significant than runoff. Measurements of the water balance of two roads in France showed that infiltration and evaporation represented up to 30% of rainfall (Ramier et al 2006).…”
Section: Depth Of Initial Losses ðDþ ¼mentioning
confidence: 99%
“…These methods will often overestimate runoff and underestimate the recharge to groundwater (Ragab et al 2003) and do not reflect the complex pattern of urban water balance in the long term. (Rodriguez et al 2005), for example, have shown that there is a considerable variation in the runoff coefficient with different rainfall conditions while (Davies & Hollis 1981) showed that when the water balance is considered over a long period, evaporation, infiltration and depression storage may be more significant than runoff. Measurements of the water balance of two roads in France showed that infiltration and evaporation represented up to 30% of rainfall (Ramier et al 2006).…”
Section: Depth Of Initial Losses ðDþ ¼mentioning
confidence: 99%
“…agricultural fields), a simple combination of the available data can be used for homogeneous zones definition (e.g. Moussa et al, 2002;Rodriguez et al, 2005;Branger, 2007 -see also Sect. 5.3.).…”
Section: Principle Of the Hydro-landscape Delineationmentioning
confidence: 99%
“…Others have used models that were conceived to give a thorough representation of storm water and wastewater dynamics [Petrucci and Bonhomme, 2014], [Zarriello, 1998] and some have resorted to more « process based » models [Rodriguez et al, 2005] (see a review in [Elliot and Trowsdale, 2007] and [Zoppou, 2001]). However, using these models at the scale of large urban conglomerations is often cumbersome.…”
Section: Introductionmentioning
confidence: 99%